Anti-fouling PP conveying belt material and preparation method thereof

By using magnetic field-assisted ultrasonic plasma spraying technology on the surface of PP conveyor belts, the problem of insufficient anti-fouling and durability of traditional conveyor belt materials is solved, and the effect of anti-fouling and wear resistance is achieved, which is suitable for high hygiene. The required industry.

CN119192649APending Publication Date: 2024-12-27QINGDAO YISU NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411304686.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional conveyor belt materials have poor performance in terms of pollution resistance and durability, especially in industries such as food processing and pharmaceutical manufacturing, and the surface of PP materials is prone to contamination to affect their service life.

Method used

The titanium dioxide-silica mixture is prepared on the surface of the PP conveyor belt through magnetic field-assisted ultrasonic plasma spraying technology. The organic silicon dioxide is prepared by electron beam radiation and polydopamine catalyzed vinyl triethoxysilane, and nanotitanium dioxide is added to form the Coating with excellent stain and wear resistance.

Benefits of technology

The hydrophilic and oleophobic effect is achieved, the anti-fouling performance is improved, and the wear resistance of the coating is significantly improved by uniform distribution and reducing pore defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005048777970000071
    Figure BDA0005048777970000071
Patent Text Reader

Abstract

The invention discloses an anti-fouling PP conveying belt material and a preparation method thereof, and relates to the field of PP conveying belts. The preparation method comprises the following steps: firstly, preparing a titanium dioxide-silicon dioxide mixed solution by utilizing an electron beam radiation processing technology to assist a sol-gel method, and then, preparing the anti-fouling PP conveying belt material by utilizing magnetic field to assist ultrasonic plasma spraying. Firstly, organic silicon dioxide is prepared through catalysis of polydopamine under electron beam radiation, the preparation time is effectively shortened, nano titanium dioxide particles are added, an oil-repellent water cushion is formed, hydrophilic and oleophobic effects are achieved, and the anti-pollution effect is improved. Secondly, the PP conveying belt is sprayed with an ultrasonic plasma spraying technology, a stable electric field is applied to assist plasma spraying, so that the composition distribution of the composite film is more uniform, the stable magnetic field can generate thermoelectric magnetic force and thermoelectromagnetic convection in the deposition process of the coating, the titanium dioxide-silicon dioxide composite film is uniformly distributed, and the coating shows excellent wear resistance. The PP conveyor belt material prepared by the invention has the effects of stain resistance and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PP conveyor belts, in particular to an anti-fouling PP conveyor belt material and a preparation method thereof. Background Art

[0002] In modern industrial production, conveyor belts are an important part of material handling, and their performance directly affects production efficiency and cost control. Especially in industries with extremely high hygiene requirements such as food processing and pharmaceutical manufacturing, conveyor belts must not only have good mechanical strength and wear resistance, but also have excellent anti-pollution capabilities to ensure the cleanliness of the production environment and the safety of products.

[0003] Traditional conveyor belt materials are mostly nylon, polyester, cotton, etc. Although these materials can meet basic usage requirements, they are not satisfactory in terms of anti-fouling and durability. For example, although the conveyor belt made of polyester canvas has the advantages of high modulus, small elongation, and fatigue resistance, it still has the problem of being easily contaminated and difficult to clean.

[0004] PP (polypropylene) materials are widely used in packaging, automobiles, construction and other fields due to their light weight, chemical resistance and easy processing. However, the surface of PP materials easily absorbs dirt, which affects its appearance and service life. Therefore, improving the anti-fouling performance of PP materials has become an important research direction in the fields of materials science, surface science and industrial design.

[0005] Therefore, the present invention provides an anti-fouling PP conveyor belt material and a preparation method thereof, which has excellent anti-fouling and wear-resistant properties. Summary of the invention

[0006] The object of the present invention is to provide an anti-fouling PP conveyor belt material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] Disclosed is an anti-fouling PP conveyor belt material, which is prepared by spraying a titanium dioxide-silicon dioxide mixed liquid onto the surface of a PP conveyor belt through magnetic field-assisted ultrasonic plasma spraying.

[0009] Furthermore, the titanium dioxide-silicon dioxide mixed liquid is prepared by using polydopamine to catalyze vinyltriethoxysilane to prepare organic silicon dioxide under electron beam radiation, and then adding nano titanium dioxide to mix.

[0010] Furthermore, a method for preparing an anti-fouling PP conveyor belt material comprises the following preparation steps:

[0011] (1) Anhydrous ethanol and vinyl triethoxysilane are mixed in a mass ratio of 1 to 1.5:1, stirred at 500 to 600 r / min for 30 to 40 min to obtain a mixed solution, a polydopamine mixed solution of 3 to 5 times the mass of the mixed solution is added, stirred at 500 to 600 r / min for 1 to 3 h, glacial acetic acid is added to adjust the pH to 6 to 7, and the mixture is placed in a PE bag;

[0012] (2) placing the PE bag under an electron beam to absorb radiation, placing it in an oven at 60° C. for 2 to 4 hours, cooling it to room temperature, adding titanium oxide powder with a particle size of 90 to 100 nm in an amount of 0.9 to 1.3 times the mass of vinyl triethoxysilane, and stirring it at 700 to 800 r / min for 30 to 60 minutes to obtain a titanium dioxide-silicon dioxide mixed solution;

[0013] (3) Placing the titanium dioxide-silicon dioxide mixed liquid in a plasma spraying system, applying a stable magnetic field, and spraying the mixed liquid onto the surface of the high-temperature resistant PP conveyor belt for 3 to 5 minutes.

[0014] Furthermore, the preparation method of the polydopamine mixed solution in step (1) is: deionized water, anhydrous ethanol and polydopamine are mixed in a mass ratio of 0.8-1.1:1.5-2:1, and stirred at 200-300 r / min for 20-30 min.

[0015] Furthermore, in step (1), placing the PE bag under an electron beam to absorb radiation is placing the PE bag under an electron beam with an irradiation voltage of 2 MeV and a dose rate of 20 kGy / pass, and the absorbed radiation dose is 50 to 100 kgy.

[0016] Furthermore, the magnetic field strength of the stable magnetic field in step (3) is 0.35-0.5T.

[0017] Furthermore, in the step (3), the plasma spraying system uses argon as the main gas, hydrogen as the auxiliary gas, and nitrogen as the powder delivery gas, wherein the flow rate of argon is 35-40 L / min, the flow rate of hydrogen is 7-10 L / min, the flow rate of nitrogen is 5-8 L / min, and the atomization pressure is 0.1-0.15 MPa.

[0018] Furthermore, in step (3), the spraying distance of the plasma spraying system is 10 to 35 mm, and the liquid flow rate is 20 to 30 mL / min.

[0019] Furthermore, in step (3), the high temperature resistant PP conveyor belt is prepared by blending glass fiber and PP fiber slices in a mass ratio of 0.25 to 0.35:1, stirring at 80 to 100 r / min for 30 to 60 min, drying at 60 to 80° C. for 18 to 24 h, melt spinning at 210 to 230° C., and then weaving into a fiber cloth.

[0020] Furthermore, in the step (3), the temperature of the high temperature resistant PP conveyor belt is maintained at 200-300° C. during the spraying process.

[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0022] The present invention uses electron beam radiation processing technology to assist the sol-gel method to prepare a titanium dioxide-silicon dioxide mixed liquid, and magnetic field-assisted ultrasonic plasma spraying to obtain an anti-fouling PP conveyor belt material, thereby achieving hydrophilic and oleophobic properties, and achieving anti-fouling and wear-resistant effects.

[0023] First, polydopamine is used to catalyze vinyltriethoxysilane to prepare organic silica under electron beam radiation. Under the action of electron beam radiation, the vinyl side groups further undergo radiation cross-linking polymerization, which effectively shortens the preparation time and improves the conversion rate of vinyltriethoxysilane. Then, nano-titanium dioxide particles are added to the mixed solution. Titanium dioxide-silica has an effective pore size and strong hydration ability, and has abundant hydroxyl groups on it, which can be used as hydrogen bond receptors to bind water molecules to form a water pad for oil repellency, which is hydrophilic and oleophobic, and improves the anti-fouling effect.

[0024] Secondly, ultrasonic plasma spraying technology is used to spray the titanium dioxide-silicon dioxide mixture onto the PP conveyor belt. When the mixture is plasmatized, high temperature and polydopamine can further catalyze the formation of silicon dioxide. At the same time, polydopamine can be used as a viscosity agent to connect titanium dioxide-silicon dioxide to the polypropylene conveyor belt. During spraying, a stable electric field is applied to assist plasma spraying. Applying a stable electric field will make the composition distribution of the titanium dioxide-silicon dioxide composite film more uniform, and the internal pore defects will be significantly reduced. The stable magnetic field will generate thermal electromagnetic force and thermal electromagnetic convection during the deposition process of the coating, resulting in a uniform distribution of the titanium dioxide-silicon dioxide composite film, so that the coating exhibits excellent wear resistance. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the anti-fouling PP conveyor belt material prepared in the following examples are as follows:

[0027] Antifouling property: The antifouling PP conveyor belt materials of the same area prepared in the embodiment and the comparative example were subjected to water contact angle test using a surface contact angle tester.

[0028] Service life: The anti-fouling PP conveyor belt materials of the embodiment and the comparative example with the same area were flushed with seawater at the same flow rate for 48 hours, and the water contact angle test was carried out using a surface contact angle tester.

[0029] Peel strength: The anti-fouling PP conveyor belt materials of the same area prepared in the embodiment and the comparative example were subjected to a peel strength test in accordance with DIN53273.

[0030] Wear resistance: The anti-fouling PP conveyor belt materials of the embodiment and the comparative example with the same area were subjected to peel strength test in accordance with GB3960-1983;

[0031] Example 1

[0032] A method for preparing an anti-fouling PP conveyor belt material comprises the following preparation steps:

[0033] (1) deionized water, anhydrous ethanol and polydopamine were mixed in a mass ratio of 0.8:1.5:1, and stirred at 200 r / min for 20 min to prepare a polydopamine mixed solution;

[0034] (2) Anhydrous ethanol and vinyl triethoxysilane were mixed in a mass ratio of 1:1, stirred at 500 r / min for 30 min to obtain a mixed solution, a polydopamine mixed solution 3 times the mass of the mixed solution was added, stirred at 500 r / min for 1 h, glacial acetic acid was added to adjust the pH to 6, and the mixture was placed in a PE bag;

[0035] (3) placing the PE bag under an electron beam with an irradiation voltage of 2 MeV and a dose rate of 20 kGy / pass, and absorbing a radiation dose of 50 kgy. After the absorption of radiation is completed, the bag is placed in an oven at 60° C. for 2 h, cooled to room temperature, and titanium oxide powder with a particle size of 90 nm and a weight of 0.9 times that of vinyl triethoxysilane is added, and stirred at 700 r / min for 30 min to obtain a titanium dioxide-silicon dioxide mixed solution;

[0036] (4) glass fiber and PP fiber slices were blended at a mass ratio of 0.25:1, stirred at 80 r / min for 30 min, dried at 60° C. for 18 h, melt-spun at 210° C., and then woven into a fiber cloth to obtain a high-temperature resistant PP conveyor belt;

[0037] (5) The titanium dioxide-silicon dioxide mixed liquid is placed in a plasma spraying system. The plasma spraying system uses argon as the main gas, hydrogen as the auxiliary gas, and nitrogen as the powder delivery gas. The flow rate of argon is 35 L / min, the flow rate of hydrogen is 7 L / min, the flow rate of nitrogen is 5 L / min, the atomization pressure is 0.1 MPa, the spraying distance is 10 mm, the liquid flow rate is 20 mL / min, and a stable magnetic field with a magnetic field strength of 0.35 T is applied. The mixed liquid is sprayed onto the surface of the high-temperature resistant PP conveyor belt. The spraying time is 3 minutes. During the spraying process, the temperature of the high-temperature resistant PP conveyor belt is maintained at 180°C.

[0038] Example 2

[0039] A method for preparing an anti-fouling PP conveyor belt material comprises the following preparation steps:

[0040] (1) Deionized water, anhydrous ethanol and polydopamine were mixed in a mass ratio of 1:1.8:1, and stirred at 250 r / min for 25 min to prepare a polydopamine mixed solution;

[0041] (2) Anhydrous ethanol and vinyl triethoxysilane were mixed in a mass ratio of 1.3:1, stirred at 550 r / min for 35 min to obtain a mixed solution, a polydopamine mixed solution of 4 times the mass of the mixed solution was added, stirred at 550 r / min for 2 h, glacial acetic acid was added to adjust the pH to 6.5, and the mixture was placed in a PE bag;

[0042] (3) placing the PE bag under an electron beam with an irradiation voltage of 2 MeV and a dose rate of 20 kGy / pass, and absorbing a radiation dose of 70 kgy. After the absorption of radiation is completed, the bag is placed in an oven at 60° C. for 3 h, cooled to room temperature, and titanium oxide powder with a particle size of 95 nm and a weight of 1.1 times that of vinyl triethoxysilane is added, and stirred at 750 r / min for 45 min to obtain a titanium dioxide-silicon dioxide mixed solution;

[0043] (4) glass fiber and PP fiber slices were blended at a mass ratio of 0.3:1, stirred at 90 r / min for 45 min, dried at 70° C. for 21 h, melt-spun at 220° C., and then woven into a fiber cloth to obtain a high-temperature resistant PP conveyor belt;

[0044] (5) The titanium dioxide-silicon dioxide mixed liquid is placed in a plasma spraying system. The plasma spraying system uses argon as the main gas, hydrogen as the auxiliary gas, and nitrogen as the powder delivery gas. The flow rate of argon is 38 L / min, the flow rate of hydrogen is 8 L / min, the flow rate of nitrogen is 6 L / min, the atomization pressure is 0.12 MPa, the spraying distance is 23 mm, the liquid flow rate is 25 mL / min, and a stable magnetic field with a magnetic field strength of 0.43 T is applied. The mixed liquid is sprayed onto the surface of the high-temperature resistant PP conveyor belt. The spraying time is 4 minutes. During the spraying process, the temperature of the high-temperature resistant PP conveyor belt is maintained at 180°C.

[0045] Example 3

[0046] A method for preparing an anti-fouling PP conveyor belt material comprises the following preparation steps:

[0047] (1) Deionized water, anhydrous ethanol and polydopamine were mixed in a mass ratio of 1.1:2:1, and stirred at 300 r / min for 30 min to prepare a polydopamine mixed solution;

[0048] (2) Anhydrous ethanol and vinyl triethoxysilane were mixed in a mass ratio of 1.5:1, stirred at 600 r / min for 40 min to obtain a mixed solution, a polydopamine mixed solution of 5 times the mass of the mixed solution was added, stirred at 600 r / min for 3 h, glacial acetic acid was added to adjust the pH to 7, and the mixture was placed in a PE bag;

[0049] (3) placing the PE bag under an electron beam with an irradiation voltage of 2 MeV and a dose rate of 20 kGy / pass, and absorbing a radiation dose of 100 kgy. After the absorption of radiation is completed, the bag is placed in an oven at 60° C. for 4 h, cooled to room temperature, and titanium oxide powder with a particle size of 100 nm and a weight of 1.3 times that of vinyl triethoxysilane is added, and stirred at 800 r / min for 60 min to obtain a titanium dioxide-silicon dioxide mixed solution;

[0050] (4) glass fiber and PP fiber slices were blended at a mass ratio of 0.35:1, stirred at 100 r / min for 60 min, dried at 80° C. for 24 h, melt-spun at 230° C., and then woven into a fiber cloth to obtain a high-temperature resistant PP conveyor belt;

[0051] (5) The titanium dioxide-silicon dioxide mixed liquid is placed in a plasma spraying system. The plasma spraying system uses argon as the main gas, hydrogen as the auxiliary gas, and nitrogen as the powder delivery gas. The flow rate of argon is 40 L / min, the flow rate of hydrogen is 10 L / min, and the flow rate of nitrogen is 8 L / min. The atomization pressure is 0.15 MPa, the spraying distance is 35 mm, the liquid flow rate is 30 mL / min, and a stable magnetic field with a magnetic field strength of 0.5 T is applied. The mixed liquid is sprayed onto the surface of the high-temperature resistant PP conveyor belt. The spraying time is 5 minutes. During the spraying process, the temperature of the high-temperature resistant PP conveyor belt is maintained at 180°C.

[0052] Comparative Example 1

[0053] The difference between Comparative Example 1 and Example 1 is that there is no step (3), and step (2) is changed to: anhydrous ethanol and vinyl triethoxysilane are mixed in a mass ratio of 1:1, stirred at 500 r / min for 30 min to obtain a mixed solution, a polydopamine mixed solution 3 times the mass of the mixed solution is added, stirred at 500 r / min for 1 h, glacial acetic acid is added to adjust the pH to 6, and then 0.9 times the mass of vinyl triethoxysilane and titanium oxide powder with a particle size of 90 nm is added, and stirred at 700 r / min for 30 min to obtain a titanium dioxide-silicon dioxide mixed solution; the remaining steps are the same as Example 1.

[0054] Comparative Example 2

[0055] The difference between Comparative Example 2 and Example 1 is that step (5) is different. Step (5) is changed to: placing the titanium dioxide-silicon dioxide mixed liquid in a plasma spraying system, the plasma spraying system uses argon as the main gas, hydrogen as the auxiliary gas, and nitrogen as the powder feeding gas, wherein the argon flow rate is 35 L / min, the hydrogen flow rate is 7 L / min, the nitrogen flow rate is 5 L / min, the atomization pressure is 0.1 MPa, the spraying distance is 10 mm, the liquid flow rate is 20 mL / min, and the mixed liquid is sprayed onto the surface of the high temperature resistant PP conveyor belt. The spraying time is 3 min, and the temperature of the high temperature resistant PP conveyor belt is maintained at 180°C during the spraying process; the remaining steps are the same as Example 1.

[0056] Comparative Example 3

[0057] The difference between Comparative Example 3 and Example 1 is that there is no step (1), and step (2) is changed to: anhydrous ethanol and vinyl triethoxysilane are mixed in a mass ratio of 1:1, stirred at 500 r / min for 30 min to obtain a mixed solution, and put into a PE bag; the remaining steps are the same as Example 1.

[0058] Comparative Example 4

[0059] The difference between Comparative Example 4 and Example 1 is that step (5) is different. Step (5) is changed to: spraying the titanium dioxide-silicon dioxide mixed liquid onto the surface of the high temperature resistant PP conveyor belt under a stable magnetic field with a magnetic field strength of 0.35T, the spraying distance is 10mm, the liquid flow rate is 20mL / min, the temperature of the high temperature resistant PP conveyor belt is maintained at 180°C during the spraying process, the spraying time is 3min, and the remaining steps are the same as Example 1.

[0060] Effect example

[0061] Table 1 below shows the performance analysis results of the anti-fouling PP conveyor belt materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0062] Table 1

[0063]

[0064] From the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 1, it can be found that under the action of electron beam radiation, the vinyl side groups will further undergo radiation cross-linking polymerization, which effectively shortens the preparation time and improves the conversion rate of silicon dioxide. Then, nano-titanium dioxide particles are added to the mixed solution. Titanium dioxide-silicon dioxide has an effective pore size and a strong hydration ability, and has abundant hydroxyl groups thereon, which can be used as hydrogen bond receptors to bind water molecules to form a water pad for oil repellency, which is hydrophilic and oleophobic, thereby improving the anti-fouling effect. From the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 2, it can be found that applying a stable electric field will make the distribution of the components of the titanium dioxide-silicon dioxide composite film more uniform, the internal pore defects are significantly reduced, and the stable magnetic The field will generate thermal electromagnetic force and thermal electromagnetic convection during the deposition process of the coating, resulting in uniform distribution of the titanium dioxide-silicon dioxide composite film, so that the coating exhibits excellent wear resistance; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 3, it can be found that polydopamine can not only catalyze the preparation of organic silicon dioxide from vinyltriethoxysilane, but also can be used as a viscous agent to connect titanium dioxide-silicon dioxide to the polypropylene conveyor belt, so that the titanium dioxide-silicon dioxide and polypropylene are more firmly bonded; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 4, it can be found that the plasma spraying has a high spraying rate and a dense coating, which makes the product more hydrophilic, has a high bonding strength with the substrate, is not easy to peel off, and has improved wear resistance.

[0065] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An anti-fouling PP conveyor belt material, characterized in that: The anti-fouling PP conveyor belt material is prepared by spraying a titanium dioxide-silicon dioxide mixed liquid onto the surface of the PP conveyor belt through magnetic field-assisted ultrasonic plasma.

2. The anti-fouling PP conveyor belt material according to claim 1, characterized in that: The titanium dioxide-silicon dioxide mixed liquid is prepared by using polydopamine to catalyze vinyltriethoxysilane to prepare organic silicon dioxide under electron beam radiation, and then adding nano titanium dioxide for mixing.

3. A method for preparing an anti-fouling PP conveyor belt material, characterized in that: The method comprises the following preparation steps: (1) Anhydrous ethanol and vinyl triethoxysilane are mixed in a mass ratio of 1 to 1.5:1, stirred at 500 to 600 r / min for 30 to 40 min to obtain a mixed solution, a polydopamine mixed solution of 3 to 5 times the mass of the mixed solution is added, stirred at 500 to 600 r / min for 1 to 3 h, glacial acetic acid is added to adjust the pH to 6 to 7, and the mixture is placed in a PE bag; (2) placing the PE bag under an electron beam to absorb radiation, placing it in an oven at 60° C. for 2 to 4 hours, cooling it to room temperature, adding titanium oxide powder with a particle size of 90 to 100 nm in an amount of 0.9 to 1.3 times the mass of vinyl triethoxysilane, and stirring it at 700 to 800 r / min for 30 to 60 minutes to obtain a titanium dioxide-silicon dioxide mixed solution; (3) Placing the titanium dioxide-silicon dioxide mixed liquid in a plasma spraying system, applying a stable magnetic field, and spraying the mixed liquid onto the surface of the high-temperature resistant PP conveyor belt for 3 to 5 minutes.

4. The method for preparing an anti-fouling PP conveyor belt material according to claim 3, characterized in that: The preparation method of the polydopamine mixed solution in step (1) is as follows: deionized water, anhydrous ethanol and polydopamine are mixed in a mass ratio of 0.8-1.1:1.5-2:1, and stirred at 200-300 r / min for 20-30 min.

5. The method for preparing an anti-fouling PP conveyor belt material according to claim 3, characterized in that: In the step (1), placing the PE bag under an electron beam to absorb radiation is to place the PE bag under an electron beam with an irradiation voltage of 2MeV and a dose rate of 20kGy / pass, and the absorbed radiation dose is 50 to 100kgy.

6. The method for preparing an anti-fouling PP conveyor belt material according to claim 3, characterized in that: The magnetic field strength of the stable magnetic field in step (3) is 0.35-0.5T.

7. The method for preparing an anti-fouling PP conveyor belt material according to claim 3, characterized in that: In the step (3), the plasma spraying system uses argon as the main gas, hydrogen as the auxiliary gas, and nitrogen as the powder feeding gas, wherein the flow rate of argon is 35-40 L / min, the flow rate of hydrogen is 7-10 L / min, the flow rate of nitrogen is 5-8 L / min, and the atomization pressure is 0.1-0.15 MPa.

8. The method for preparing an anti-fouling PP conveyor belt material according to claim 3, characterized in that: In the step (3), the spraying distance of the plasma spraying system is 10 to 35 mm, and the liquid flow rate is 20 to 30 mL / min.

9. The method for preparing an anti-fouling PP conveyor belt material according to claim 3, characterized in that: In step (3), the high temperature resistant PP conveyor belt is prepared by blending glass fiber and PP fiber slices in a mass ratio of 0.25 to 0.35:1, stirring at 80 to 100 r / min for 30 to 60 min, drying at 60 to 80° C. for 18 to 24 h, melt spinning at 210 to 230° C., and then weaving into a fiber cloth.

10. The method for preparing an anti-fouling PP conveyor belt material according to claim 3, characterized in that: In the step (3), the temperature of the high temperature resistant PP conveyor belt is maintained at 180-300° C. during the spraying process.